Efektivitas Manajemen Sekolah Adiwiyata Mandiri (Studi di SMP Negeri 1 Tanjung Morawa Kabupaten Deli Serdang) - Rahayu, Nining Esti; Dongoran, Faisal Rahman (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
This study aims to evaluate the planning and implementation of the independent Adiwiyata School program at SMP Negeri 1 Tanjung Morawa based on the regulations of the Ministry of Environment. The research method utilizes interviews, observations, and documentation to collect data related to the planning of the PBLHS Movement activities (Adiwiyata Program). The results indicate the effectiveness of the planning that involves various aspects, such as policy development, environmentally-based curriculum, and participatory environmentally-based activities, as well as the management of environmentally friendly school facilities. Active participation of all stakeholders, including the school principal, educators, school committee, students, and the community, in the development of the PBLHS Movement Plan reflects comprehensive involvement. The integration of this plan into the Lesson Implementation Plan (RPP) and the School Activity and Budget Plan (RKAS) demonstrates financial commitment to the program. The research also highlights the implementation of the School Environmental Behavior Program (PRLH), which includes cleanliness activities, waste management, tree planting, water and energy conservation, as well as creative waste-based innovations. Although the program involves the entire school community and the public, the evaluation indicates that the implementation has not reached an optimal level. Supervision and program evaluation are conducted through internal and external monitoring, with the involvement of all stakeholders. Although the management of the Adiwiyata school is considered effective, the evaluation still has the potential for improvement to achieve more optimal results. The positive findings of this research provide a comprehensive overview of the implementation of the Adiwiyata program at SMP Negeri 1 Tanjung Morawa, while highlighting areas for improvement that can be applied to enhance the effectiveness of the program in the future.